Effect of a probiotic beverage consumption (Enterococcus faecium CRL 183 and Bifidobacterium longum ATCC 15707) in rats with chemically induced colitis - Celiberto, Larissa Sbaglia [UNESP]; Bedani, Raquel; Dejani, Naiara Naiana [UNESP]; De Medeiros, Alexandra Ivo [UNESP]; Zuanon, José Antonio Sampaio [UNESP]; Spolidorio, Luis Carlos [UNESP]; Adorno, Maria Angela Tallarico; Varesche, Maria Bernadete Amâncio; Galvão, Fábio Carrilho [UNESP]; Valentini, Sandro Roberto [UNESP]; De Valdez, Graciela Font; Rossi, Elizeu Antonio [UNESP]; et al. (Public Library of Science (PLoS), 2017)
Background Some probiotic strains have the potential to assist in relieving the symptoms of inflammatory bowel disease. The impact of daily ingestion of a soy-based product fermented by Enterococcus faecium CRL 183 and Lactobacillus helveticus 416 with the addition of Bifidobacterium longum ATCC 15707 on chemically induced colitis has been investigated thereof within a period of 30 days. Methods Colitis was induced by dextran sulfate sodium. The animals were randomly assigned into five groups: Group C: negative control; Group CL: positive control; Group CLF: DSS with the fermented product; Group CLP: DSS with the non-fermented product (placebo); Group CLS: DSS with sulfasalazine. The following parameters were monitored: disease activity index, fecal microbial analyses, gastrointestinal survival of probiotic microorganisms and short-chain fatty acids concentration in the feces. At the end of the protocol the animals' colons were removed so as to conduct a macroscopical and histopathological analysis, cytokines and nitrite quantification. Results Animals belonging to the CLF group showed fewer symptoms of colitis during the induction period and a lower degree of inflammation and ulceration in their colon compared to the CL, CLS and CLP groups (p<0.05). The colon of the animals in groups CL and CLS presented severe crypt damage, which was absent in CLF and CLP groups. A significant increase in the population of Lactobacillus spp. and Bifidobacterium spp. at the end of the protocol was verified only in the CLF animals (p<0.05). This group also showed an increase in short-chain fatty acids (propionate and acetate). Furthermore, the intestinal survival of E. faecium CRL 183 and B. longum ATCC 15707 in the CLF group has been confirmed by biochemical and molecular analyzes. Conclusions The obtained results suggest that a regular intake of the probiotic product, and placebo to a lesser extent, can reduce the severity of DSS-induced colitis on rats.